A Mathematical Model Based Study on the Dynamics of Corona Virus (COVID-19) Disease Spread in Population - Verma, Vinay (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we have proposed an $SEIHRV$ mathematical model of the pandemic COVID-19 using a system of ordinary differential equations. The mathematical modelling is a vital tool to make the use of imposing a strategy in order to fight against this pandemic. We are obtained a boundedness of the system and steady state of the solutions. The basic reproduction number is computed and used as a threshold to negotiate the asymptotic behavior of the mathematical model. Our analytical and numerical results show a close faith of the basic reproduction number on epidemic parameters. Also, our model delineates the various transmission route in the infection dynamics and an exertion the foreword of the environmental reservoir in the devolution and the dispersion of this disease.